2020
DOI: 10.1111/mec.15703
|View full text |Cite
|
Sign up to set email alerts
|

Elevated rates of positive selection drive the evolution of pestiferousness in the Colorado potato beetle (Leptinotarsa decemlineata, Say)

Abstract: Contextualizing evolutionary history and identifying genomic features of an insect that might contribute to its pest status is important in developing early detection and control tactics. In order to understand the evolution of pestiferousness, which we define as the accumulation of traits that contribute to an insect population's success in an agroecosystem, we tested the importance of known genomic properties associated with rapid adaptation in the Colorado potato beetle (CPB), Leptinotarsa decemlineata Say.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 142 publications
0
27
0
Order By: Relevance
“… a Among these genes, three (the CYP gene LDEC015048, the cuticle protein LDEC010803, and the voltage-dependent calcium channel gene LDEC000112) were found as candidate genes among field populations within Wisconsin ( Crossley et al 2017 ). The nicotinic acetylcholine receptor subunit alpha4 (LDEC007707) was also found as a candidate gene in a comparative genomic analysis of Leptinotarsa by Cohen et al (2021) . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Among these genes, three (the CYP gene LDEC015048, the cuticle protein LDEC010803, and the voltage-dependent calcium channel gene LDEC000112) were found as candidate genes among field populations within Wisconsin ( Crossley et al 2017 ). The nicotinic acetylcholine receptor subunit alpha4 (LDEC007707) was also found as a candidate gene in a comparative genomic analysis of Leptinotarsa by Cohen et al (2021) . …”
Section: Resultsmentioning
confidence: 99%
“… Schoville et al (2018) found evidence for a high rate of polymorphism in protein-coding regions of CPB (nucleotide diversity, π , was ∼0.01), suggesting a high level of standing genetic diversity and large effective size. Furthermore, CPB shows a larger effective size, higher rate of positive selection, and greater levels of standing variation compared with other species in the genus Leptinotarsa ( Cohen et al 2021 ). In this study, irrespective of pest or nonpest status across different geographical regions, we identify an average genome-wide nucleotide diversity of 0.005 within CPB.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…From early insecticides such as Paris Green and DDT, to modern insecticides such as pyrethroids and neonicotinoids, CPB populations have accumulated resistance over impressively short periods of time, even within one year (∼2-3 generations) of the introduction of novel chemicals (Forgash 1985, Ioannidis et al 1991, Alyokhin et al 2008; Brevik et al, 2018). In a species-level comparative genomic analysis, CPB shows a higher rate of positive selection on putative insecticide resistant loci compared to other species in the genus Leptinotarsa (Cohen et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of genome-wide genetic variation are influenced by mutation, recombination, and selection, in direct relationship to effective population size (Hartl and Clark 1997). Prior work suggests that CPB has relatively high genome-wide standing genetic variation (Schoville et al, 2018; Cohen et al, 2020; Pélissié et al, 2022), yet it remains unclear how population history, recombination, and selection interact to shape this variation. Here, we examine the influence of demography and recombination on selection between two highly resistant geographically distinct pest CPB populations in the United States.…”
Section: Introductionmentioning
confidence: 99%